Causes and Consequences of Sports Concussion. Issue 2 (2014) - Edwards, Jonathan C.; Bodle, Jeffrey D.
Abstract : The Consensus Statement of the Third International Congress on Concussion in Sport in November 2008 defined concussion as a "complex pathophysiologic process affecting the brain, induced by traumatic biochemical forces." Definitions of concussion vary slightly between various professional organizations of neurosurgeons, neurologists, and orthopedic surgeons, but all share the common characteristics of trauma affecting the head or body resulting in transient neurologic deficits or symptoms. Underlying the symptoms of concussion is a complex pathophysiologic process at the cellular level. While concussion is typically thought of as resulting from a direct impact to the head, a concussion can also be sustained as a result of an impact to the body causing the force of the impact to be transmitted to and absorbed by the brain.